NGATHA-LIKEs Control Leaf Margin Development by Repressing CUP-SHAPED COTYLEDON2 Transcription. Issue 1 (1st July 2020) - Shao, Jingxia; Meng, Jingjing; Wang, Feng; Shou, Bidong; Chen, Yu; Xue, Hui; Zhao, Jun; Qi, Yafei; An, Lijun; Yu, Fei; Liu, Xiayan
Abstract : Arabidopsis NGATHA-LIKE transcription factors repress the transcription of CUP-SHAPED COTYLEDON2 gene and inhibit the formation of serrations along the leaf margin. Abstract: The leaf margin is a fascinating feature of leaf morphology, contributing to the incredible diversity of leaf shapes and forms. As a central regulator of plant organ separation and margin development, CUP-SHAPED COTYLEDON2 (CUC2), a NAM, ATAF1, 2, CUC2 (NAC)-family transcription factor, governs the extent of serrations along the leaf margin. CUC2 activity is tightly regulated at transcriptional and posttranscriptional levels. However, the molecular mechanism that controls CUC2 transcription during leaf development has not been fully elucidated. Here we report that Arabidopsis ( Arabidopsis thaliana ) NGATHA-LIKE1 (NGAL1) to NGAL3, which are three related B3 family transcription factors, act as negative regulators of leaf margin serration formation. Over-expression of NGALs led to "cup-shaped" cotyledons and smooth leaf margins, whereas the triple loss-of-function mutant ngaltri exhibited more serrated leaves than the wild type. RNA-sequencing analyses revealed that the expression levels of a number of transcription factor genes involved in leaf development are regulated by NGALs, including CUC2 . Comparative transcriptome analyses further uncovered a significant overlap between NGAL- and CUC2-regulated genes. Moreover, genetic analyses using various combinations of gain- and loss-of-function mutants of NGALs and CUC2 confirmed that CUC2 acts downstream of NGALs in promoting the formation of leaf-margin serrations. Finally, we demonstrate that NGAL1 directly binds to the CUC2 promoter causing repressed CUC2 expression. In summary, direct CUC2 transcriptional repression by NGAL1 characterizes a further regulatory module controlling leaf margin development.